(untitled) (Journal of history, 2023)
This article discusses the Soviet state’s policy of conducting mass deportations to Kazakhstan based on people’s ethnic background. The aim of the presented article is to study the forced resettlement of specific peoples to the territory of Eastern Kazakhstan, using oral history as a method and source of historical research. The primary sources of the article are field research materials conducted in the Eastern Kazakhstan region. The value of the collected field materials is determined by introducing new factual material of personal origin into the field of science. It is noted that the field materials gathered through interviews with informants allow for supplementing and specifying the events of the domestic history of the 20th century. Based on official documents, archival sources, and oral history materials, this study examines the population and resettlement of special settlers, the course, scale, and consequences of deportation, as well as the adaptation and survival of these special settlers through the lens of individual and collective memory. Through the analysis of the data, it is noted that the recollections of deportation witnesses and their descendants can be regarded as one of the forms of transmitting collective memory. The authors conclude that referencing the historical memory of witnesses of forced migrations and their descendants allows for identifying the peculiarities of political, demographic, and ethnic processes within the studied region. Key words: deportation, ethnic groups, Germans, Chechens, historical memory, special settlers.